2021
DOI: 10.1038/s41598-021-98473-z
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of uterine low-grade endometrial stromal sarcoma from rare leiomyoma variants by magnetic resonance imaging

Abstract: The purpose of this study is to evaluate utility of MRI in differentiation of uterine low-grade endometrial stromal sarcoma (LGESS) from rare leiomyoma variants. This multi-center retrospective study included consecutive 25 patients with uterine LGESS and 42 patients with rare leiomyoma variants who had pretreatment MRI. Two radiologists (R1/R2) independently evaluated MRI features, which were analyzed statistically using Fisher’s exact test or Student's t-test. Subsequently, using a five-point Likert scale, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(49 reference statements)
0
3
0
1
Order By: Relevance
“… 3 Additionally, the solid component of a low-grade ESS often appears relatively homogeneous, without the speckled appearance, commonly observed in typical leiomyomas. 4 The homogeneous solid component, along with the frequent occurrence of cystic degeneration, as demonstrated in this case, can be a valuable clue in the differential diagnosis of a low-grade ESS. 4 …”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“… 3 Additionally, the solid component of a low-grade ESS often appears relatively homogeneous, without the speckled appearance, commonly observed in typical leiomyomas. 4 The homogeneous solid component, along with the frequent occurrence of cystic degeneration, as demonstrated in this case, can be a valuable clue in the differential diagnosis of a low-grade ESS. 4 …”
Section: Discussionmentioning
confidence: 61%
“… 4 The homogeneous solid component, along with the frequent occurrence of cystic degeneration, as demonstrated in this case, can be a valuable clue in the differential diagnosis of a low-grade ESS. 4 …”
Section: Discussionmentioning
confidence: 61%
“…Los SEE-BG deben diferenciarse de otros tipos de diferenciación, como focal de tipo músculo liso, rabdoide focal o estructuras tipo cordones sexuales (10) . Además, otros diagnósticos diferenciales incluyen al leiomioma epitelioide, leiomiosarcoma epitelioide, PEComa, tumor mülleriano mixto y metástasis de tumor de cordones sexuales ovárico (13) .…”
Section: Discussionunclassified
“… 53 To differentiate ESS from LM variants, the ADC value is a useful tool. Himoto et al 54 showed that the cutoff values of 0.932 and 0.776 × 10 −3 mm 2 /s using the mean value of 3 circular ROIs of >25 mm 2 resulted in sensitivities of 78% and 89% and specificities of 76% and 65%, respectively, for differentiating ESS from LM variants. However, similar to LMS, some overlap between ESS and rare LM variants was observed due to hypercellularity.…”
Section: Myometrial Tumorsmentioning
confidence: 99%